Problems of Cultural Tourism Development and Trends of its Development in the City of Samarkand - Sattarova Z. I. (International Journal on Integrated Education, 2022)
The global spread of the outbreak of a new coronavirus disease (COVID-19) in early 2020 has seriously affected the tourism sector. In the period from January 2020 to May 2021, the number of international tourist arrivals decreased by 56%. The Asia-Pacific region suffered the most: during the same period, the number of tourists decreased by 60%. The United Nations World Tourism Organization (UNWTO) estimates that the overall reduction in the number of international tourist arrivals worldwide in 2023 could range from 58% to 78%, depending on when travel restrictions are lifted. This will lead to the loss of export revenues from tourism in the amount of $910 to $1.2 trillion and could endanger up to 120 million jobs in the tourism industry. It is expected that although domestic tourism will recover faster, regional and international travel will not show any signs of recovery until 2025